Incidence of medically attended influenza during pandemic and post-pandemic seasons through the Influenza Incidence Surveillance Project, 2009–13. Issue 9 (September 2015) - Fowlkes, Ashley; Steffens, Andrea; Temte, Jon; Lonardo, Steve Di; McHugh, Lisa; Martin, Karen; Rubino, Heather; Feist, Michelle; Davis, Carol; Selzer, Christine; Lojo, Jose; Oni, Oluwakemi; et al.
Summary: Background: Since the introduction of pandemic influenza A (H1N1) to the USA in 2009, the Influenza Incidence Surveillance Project has monitored the burden of influenza in the outpatient setting through population-based surveillance. Methods: From Oct 1, 2009, to July 31, 2013, outpatient clinics representing 13 health jurisdictions in the USA reported counts of influenza-like illness (fever including cough or sore throat) and all patient visits by age. During four years, staff at 104 unique clinics (range 35–64 per year) with a combined median population of 368 559 (IQR 352 595–428 286) attended 35 663 patients with influenza-like illness and collected 13 925 respiratory specimens. Clinical data and a respiratory specimen for influenza testing by RT-PCR were collected from the first ten patients presenting with influenza-like illness each week. We calculated the incidence of visits for influenza-like illness using the size of the patient population, and the incidence attributable to influenza was extrapolated from the proportion of patients with positive tests each week. Findings: The site-median peak percentage of specimens positive for influenza ranged from 58·3% to 77·8%. Children aged 2 to 17 years had the highest incidence of influenza-associated visits (range 4·2–28·0 per 1000 people by year), and adults older than 65 years had the lowest (range 0·5–3·5 per 1000 population). Influenza A H3N2, pandemic H1N1, and influenza B equally co-circulated in the first post-pandemic season, whereas H3N2 predominated for the next two seasons. Of patients for whom data was available, influenza vaccination was reported in 3289 (28·7%) of 11 459 patients with influenza-like illness, and antivirals were prescribed to 1644 (13·8%) of 11 953 patients. Interpretation: Influenza incidence varied with age groups and by season after the pandemic of 2009 influenza A H1N1. High levels of influenza virus circulation, especially in young children, emphasise the need for additional efforts to increase the uptake of influenza vaccines and antivirals. Funding: US Centers for Disease Control and Prevention.